Novel TP53RK variants cause varied clinical features of Galloway–Mowat syndrome without nephrotic syndrome in three unrelated Chinese patients - Chen, Jing; Ye, Gao-Bo; Huang, Jin-Rong; Peng, Min; Gu, Wei-Yue; Xiong, Pin; Zhu, Hong-min (Frontiers in Molecular Neuroscience, 2023)
Objectives Galloway–Mowat syndrome-4 (GAMOS4) is a very rare renal-neurological disease caused by TP53RK gene mutations. GAMOS4 is characterized by early-onset nephrotic syndrome, microcephaly, and brain anomalies. To date, only nine GAMOS4 cases with detailed clinical data (caused by eight deleterious variants in TP53RK) have been reported. This study aimed to examine the clinical and genetic characteristics of three unrelated GAMOS4 patients with TP53RK gene compound heterozygous mutations. Methods Whole-exome sequencing (WES) was used to identify four novel TP53RK variants in three unrelated Chinese children. Clinical characteristics such as biochemical parameters and image findings of patients were also evaluated. Furthermore, four studies of GAMOS4 patients with TP53RK variants were reviewed. In addition, clinical and genetic features were described after a retrospective analysis of clinical symptoms, laboratory data, and genetic test results. Results The three patients showed facial abnormalities, developmental delays, microcephaly, and aberrant cerebral imaging. Furthermore, patient 1 had slight proteinuria, while patient 2 had epilepsy. However, none of the individuals had nephrotic syndrome, and all were alive for more than 3 years of age. This is the first study to assess four variants in the TP53RK gene (NM_033550.4: c.15_16dup/p.A6Efs*29, c.745A > G/p.R249G, c.185G > A/p.R62H, and c.335A > G/p.Y112C). Conclusion The clinical characteristics of the three children with TP53RK mutations are significantly different from the known GAMOS4 traits, including early nephrotic syndrome and mortality mainly occurring in the first year of life. This study provides insights into the pathogenic TP53RK gene mutation spectrum and clinical phenotypes of GAMOS4.